Cytokine concentration in aqueous humour of eyes with exudative age-related macular degeneration - Jonas, Jost B.; Neumaier, Michael; Findeisen, Peter (Acta ophthalmologica, 2012)
Abstract. Purpose: To measure the concentration of cytokines in the aqueous humour of eyes with exudative age-related macular degeneration (AMD). Methods: The clinical interventional study included a study group of 18 patients with exudative AMD and a control group of 20 patients undergoing routine cataract surgery. Age did not vary significantly (p = 0.36) between study group (80.8 ± 6.4 years) and control group (77.0 ± 9.9 years), nor did gender (p = 0.75). During the interventions, aqueous humour samples were obtained, in which the concentration of cytokines was measured using a solid-phase chemiluminescence immunoassay. Macular thickness was measured by optical coherence tomography (OCT). Results: In the study group as compared to the control group, significantly higher concentrations were measured for epithelial growth factor (EGF) (p = 0.017), human growth factor (HGF) (p = 0.048), intercellular adhesion molecule-1 (ICAM1) (p = 0.028), interleukin 12p40 (IL12p40) (p = 0.009), interleukin 1a2 (IL1a2) (p = 0.01), interleukin 3 (IL3) (p = 0.02), interleukin 6 (IL6) (p = 0.006), interleukin 8 (IL8) (p = 0.02), monocyte chemoattractant protein-1 (MCP-1) (p = 0.048), monokine induced by interferon gamma (MIG) (p = 0.016), matrix metalloproteinase 9 (MMP9) (p = 0.004) and plasminogen activator inhibitor 1 (PAI1) (p = 0.006). Macular thickness was significantly associated with the concentrations of EGF (p = 0.001), HGF (p = 0.02), ICAM1 (p = 0.001), interleukin 12p40 (p = 0.006), IL 1a2 (p = 0.002), MIG (p = 0.001), MMP9 (p < 0.001) and PAI1 (p = 0.01). Interleukin 6 and MCP-1 showed significant associations with the height of retinal pigment epithelium detachment. Conclusions: Numerous cytokines are associated with the presence and the amount of exudative AMD.